Investigating the Influence of Trust, Attractiveness, Perceived Expertise, and Perceived Credibility on Attitude Toward the Influencer: The Mediating Role of Attitude Toward the Influencer and Moderating Role and Perceived Risks (KASBIT Business Journal, 2023)
In recent years, influencer marketing has become an important part of firms' strategic communication. This is mostly due to the declining effectiveness of conventional media channels for communication. The purpose of this study is to find out the impact of trust, attractiveness, perceived expertise, and perceived credibility on the consumer's attitude toward influencers. Moreover, the study examines the mediating role of attitude toward the influencer and the moderating role of perceived risks. The study employed a quantitative research design and data were collected from 250 social media users. PLS-SEM was used for data analysis and hypothesis testing. The findings indicated that perceived credibility, perceived expertise, and attractiveness positively and significantly impact attitudes towards influencers which further significantly and positively mediates the relationship of the three independent variables with purchase intention. The impact of trust on attitude towards influencer was found to be insignificant as well as the mediating role of attitude towards influencer in the relationship between trust and purchase intention. This study aims to provide insights to fashion marketers and advertisers that may improve influencer relationships by understanding how trust, attractiveness, knowledge, and credibility affect consumer perceptions. To create and maintain strong influencer-consumer interactions, risk mitigation measures are needed to moderate perceived dangers. This study illuminates the intricate relationships between trust, attractiveness, perceived expertise, perceived credibility, attitudes toward influencers, and perceived dangers to improve our knowledge of influencer-consumer dynamics. These insights help create more effective influencer marketing campaigns and strengthen influencer-audience relationships in the changing digital marketing landscape.
Keywords: Perceived Expertise; Attractiveness; Perceived credibility; Attitude towards influencers; Perceived Risks; Fashion influencers; Purchase intention